O-168 Chronic pelvic pain is the most troublesome endometriosis pain symptom for women's quality of life. (6th August 2021) - Pijpops, P; Apers, S; Meuleman, C; Tomassetti, C; Dancet, E
Abstract: Study question: Which pre-operative endometriosis pain symptom is most troublesome for the quality-of-life of women assessed at different meta-levels? Summary answer: Of five pain symptoms chronic pelvic pain is most troublesome or has the strongest correlation to women's overall quality-of-life and overall and endometriosis-specific health status. What is known already: Endometriosis affects women's quality of life negatively, and its impact seems to depend more on women's symptoms than on their degree of endometriosis. Experts proposed to include 'the most troublesome symptom' and 'overall pain' as core outcomes but did not define how to assess these outcomes. It would be interesting to find out which pain symptom (i.e. assessed for presence and intensity) has most impact on women's quality-of-life assessed at different meta-levels, including: overall quality-of-life (depending on amongst others one's professional and relational life besides health), general health status and endometriosis-specific health status. Study design, size, duration: A prospective survey addressed 277 adult women scheduled for diagnostic and/or therapeutic surgery in a University endometriosis clinic between October 2016 and November 2019. Women were reminded twice of our request to fill out the coded but anonymous questionnaire package assessing five pain symptoms (i.e. chronic pelvic pain, dysmenorrhea, dyspareunia, dysuria and dyschezia) and assessing quality-of-life at three different meta-levels. Participants/materials, setting, methods: Women scored five endometriosis symptoms between 0 (no pain) and 10 (worst imaginable pain), combined into 'overall pain' (0-50). 'Overall quality-of-life' was assessed with the Linear Analogue Scale (LAS; the higher, the better). General and endometriosis-specific health status were assessed with the overall scores of the EuroQol-5D and the Endometriosis-Health-Profile-30 (the higher, the better). Pearson correlation coefficients between the six pain scores and three measures of quality-of-life were computed (p = 0.003; 0.05/18 as Bonferroni correction). Main results and the role of chance: A total of 227 women took part (participation rate=82%) and the data of 202 women (mean age 31±5 years old) with surgically confirmed endometriosis were analysed. In the previous six months, the majority of women reported chronic pelvic pain (56%), dyspareunia (55%), dysmenorrhea (56%) and/or dyschezia (58.4%), while only some reported dysuria (25%). Women's mean overall pain score was 20 (±12). Women's mean overall quality-of-life was 65 (±16). On average women rated their general health status to be 62 (±18) and their mean endometriosis-specific health status was 53 (±18). Only the pain symptom chronic pelvic pain was correlated (p < 0.001) to assessments of quality-of-Life at all three meta-levels. The correlation for endometriosis-specific health status was large (r= -0.574), while the others were medium (r= -0.343 & r= -0.324). After taking account of the Bonferroni correction for multiple testing the remaining four pain symptoms only had a medium correlation (p < 0.001) to endometriosis-specific health status (r= -0.356 – -0.265; p < 0.001) and they were not correlated to overall quality-of-Life or general health status. Overall pain had a medium correlation (p < 0.001) to Overall quality-of-Life (r= -0.270) and general health status (r= -0.259) and a strong correlation (p < 0.001) to endometriosis-specific health status (r= -0.529). Limitations, reasons for caution: The majority of patients (60%) of the recruiting University endometriosis clinic had severe endometriosis (AFS-IV) and this study could be repeated in another setting. Directly asking women which pain symptom is most troublesome to them would be interesting besides exploring correlations between pain symptoms and quality of life. Wider implications of the findings: Nurses, midwives and other health care professionals should devote attention to chronic pelvic pain during the anamnesis and women-centred care as this pain symptom is most troublesome for women's quality of life. Whether surgery decreases chronic pelvic pain and overall pain is currently followed-up in the studied prospective cohort. Trial registration number: Not applicable